2010
DOI: 10.1016/j.jtcvs.2009.11.059
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracic surgery versus open lobectomy for lung cancer: A secondary analysis of data from the American College of Surgeons Oncology Group Z0030 randomized clinical trial

Abstract: Patients undergoing video-assisted lobectomy had fewer respiratory complications and shorter length of stay. These data suggest video-assisted thoracoscopic lobectomy is safe in patients with resectable lung cancer. Longer follow-up is needed to determine the oncologic equivalency of video-assisted versus open lobectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
228
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(251 citation statements)
references
References 17 publications
12
228
0
11
Order By: Relevance
“…In fact, thoracoscopic surgery is the preferred approach for lung anatomic resection in current practice guidelines for the treatment of early-stage lung cancer (1,2) as well as for most benign intrathoracic pathologies. Benefits include decreased blood loss, decreased pain, shorter length of hospital stay and fewer complications (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, thoracoscopic surgery is the preferred approach for lung anatomic resection in current practice guidelines for the treatment of early-stage lung cancer (1,2) as well as for most benign intrathoracic pathologies. Benefits include decreased blood loss, decreased pain, shorter length of hospital stay and fewer complications (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…For patients requiring a lobectomy, studies have demonstrated equivalence in morbidity, mortality, and oncologic outcome at 5 years (5)(6)(7)(8). Some areas such as length of stay and cost may even be superior in VATS (7,9).…”
Section: Vatsmentioning
confidence: 99%
“…For patients requiring a lobectomy, studies have demonstrated equivalence in morbidity, mortality, and oncologic outcome at 5 years (5)(6)(7)(8). Some areas such as length of stay and cost may even be superior in VATS (7,9). There are still areas where the appropriateness of VATS is less defined such as for late-stage lung cancer, VATS sleeve lobectomy, thoracic trauma, rib resections, or low-resource medical environments (10)(11)(12).…”
Section: Vatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows a list of previously performed randomized, controlled studies and recent cohort-matched studies. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Thoracoscopic surgery was superior to thoracotomy in many reports with regard to the duration of drainage period, postoperative complications, operative mortality rate, and length of hospital stay. The postoperative mortality rate after thoracoscopic surgery is comparable to that after thoracotomy, but the postoperative complication rate was lower in thoracoscopic surgery, resulting in a short hospital stay in many reports.…”
Section: Thoracoscopic Lobectomy For Primary Lung Cancermentioning
confidence: 99%